Aboriginal Workplace Integration in Northern Canada - Hesseln, Hayley; Hall, Heather (Journal of Aboriginal Economic Development, 2017)
Economic development requires skilled labour yet Indigenous people face persistent educational and labour market challenges across northern Canada. Systemic problems are widely known and relate to political funding cycles, short-term programming, and the lack of collaboration among key stakeholders. Such barriers are not only consistent across northern territorial and provincial jurisdictions, but they are widely known and well-documented. Research and stakeholder interviews suggest that barriers to education and successful transition to the labour market are a result of disjointed and short-term educational and skills-training programs that do not recognize the importance of fully supporting the learner, their families, and their communities. This paper identifies and examines best practices aimed to close the gap between education and skills training to meet successful long-term employment goals. Specifically, we suggest that using a holistic approach to training could help to advance economic development goals that promote Aboriginal participation in the market economy.